2009
DOI: 10.1121/1.3113892
|View full text |Cite
|
Sign up to set email alerts
|

The pitch levels of female speech in two Chinese villages

Abstract: Abstract:The pitch levels of female speech in two villages situated in a relatively remote area of China were compared. The dialects spoken in the two villages are similar to Standard Mandarin, and all subjects had learned to read and speak Standard Mandarin at school. Subjects read out a passage of roughly 3.25 min in Standard Mandarin, and pitch values were obtained at 5-ms intervals. The overall pitch levels in the two villages differed significantly, supporting the conjecture that pitch levels of speech ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 16 publications
0
21
0
2
Order By: Relevance
“…Torgerson, 2005;Deutsch et al, 2009;Huang and Fon, 2011, inter alia), it is not surprising that it has also been found to vary as a function of language (see Dolson, 1994, for a review). However, we do not know enough about what factors or combination of factors are responsible for this differentiation as very few comparative studies have been carried out on pitch range differences between languages or language varieties .…”
Section: Cross-language Variation In Pitch Rangementioning
confidence: 99%
“…Torgerson, 2005;Deutsch et al, 2009;Huang and Fon, 2011, inter alia), it is not surprising that it has also been found to vary as a function of language (see Dolson, 1994, for a review). However, we do not know enough about what factors or combination of factors are responsible for this differentiation as very few comparative studies have been carried out on pitch range differences between languages or language varieties .…”
Section: Cross-language Variation In Pitch Rangementioning
confidence: 99%
“…In the absence of organic factors which could potentially be the source of such differences (e.g., body size or race-based vocal tract differences, Awan and Mueller, 1996), investigators have attributed cross-language differences to either linguistic or cultural factors, but there has been little attempt to characterize the phonetic basis of these differences (Deutsch et al, 2009) nor to question the suitability of the f0 measures used. For example, Majewski et al (1972) found higher mean f0 in young Polish males compared to previously reported values for American males.…”
Section: Introductionmentioning
confidence: 99%
“…An example of the former would be studies looking at the scaling of tones in the phonetic realization of intonation, where a central issue is how to capture tonal invariance in the face of variation in pitch range (e.g., Dilley and Brown, 2007;Hirschberg and Ward, 1992;Liberman and Pierrehumbert, 1984). Examples of the latter include clinical studies investigating the extent to which various clinical populations have atypical prosody (e.g., Diehl, Watson, Bennetto, Mcdonough, and Gunlogson, 2009;Hubbard and Trauner, 2007), studies of the vocal correlates of affect (e.g., Banse and Scherer, 1996;Ladd, Silverman, Tolkmitt, Bergmann, and Scherer, 1985;Sobin and Alpert, 1999), and studies of various speaker-oriented factors such as the effects of age, gender, height and weight, ethnicity, and regional accent on f0 (Chen, 2005;Deutsch, Le, Shen, and Henthorn, 2009;Hollien, Hollien, and de Jong, 1997;Nishio and Niimi, 2008;Van Bezooijen, 1995;Van Dommelen and Moxness, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The influence of culture on voice was explored in populations who spoke the same language, but differed in their cultural or ethnic backgrounds. Following voice analysis, research conclusions indicated differences in vocal parameters between cultural populations, particularly in fundamental frequency (F0) and perturbation measures, which confirms the role of sociocultural elements in the varying measures of voice output (19)(20)(21) . Cross-population studies that have looked at the effect of language on vocal features have also discovered differences, primarily in mean F0 and fundamental frequency range.…”
Section: Introductionmentioning
confidence: 88%
“…There has been growing research on the effects of language on voice characteristics (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) . When listeners were asked to discriminate whether two speech samples were produced by the same bilingual speaker, listeners were less accurate in their judgment when the speaker switched between English and Finnish, English and German and English and Mandarin as compared to matched-language samples (e.g.…”
Section: Introductionmentioning
confidence: 99%